(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
It is known that pumpkin fruits have a rich mineral and vitamin content. The pulp of pumpkin fruits is rich in dietary fibers; therefore, they are used in the production of a wide range of functional food products. In this article, a technological scheme for producing a nutritious, functional drink from pumpkin fruits is developed. The amount of dry matter in the resulting drinks is equal to 14%, which fully satisfies the daily consumption of these substances.